The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/stem.3113
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles transmit epithelial growth factor activity in the intestinal stem cell niche

Abstract: Extracellular vesicles (EV) are membrane-surrounded vesicles that represent a novel way of intercellular communication by carrying biologically important molecules in a concentrated and protected form. The intestinal epithelium is continuously renewed by a small proliferating intestinal stem cell (ISC) population, residing at the bottom of the intestinal crypts in a specific microenvironment, the stem cell niche. By using 3D mouse and human intestinal organoids, we show that intestinal fibroblast-derived EVs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…Interestingly, CAFs critically contribute to the cellular heterogeneity of CRC and to the acquision of the aggressive cancer stem cell phenotype ( Vermeulen et al, 2010 ; Essex et al, 2019 ). In addition, we found that intestinal fibroblast-derived EVs carry amphiregulin (AREG), a member of the EGF ligand family, and EVs have a central role in shaping the intestinal stem cell niche ( Oszvald et al, 2020 ). However, the role of EVs as conveyors of messages in the stroma-CRC cell communication is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CAFs critically contribute to the cellular heterogeneity of CRC and to the acquision of the aggressive cancer stem cell phenotype ( Vermeulen et al, 2010 ; Essex et al, 2019 ). In addition, we found that intestinal fibroblast-derived EVs carry amphiregulin (AREG), a member of the EGF ligand family, and EVs have a central role in shaping the intestinal stem cell niche ( Oszvald et al, 2020 ). However, the role of EVs as conveyors of messages in the stroma-CRC cell communication is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Due to better mimic of the skin environment, some researchers reported that ASCs lifted to ALI showed a satisfactory differentiation [16]. Otherwise, differentiation of stem cells depends on the "niche," including diffusible paracrine effects, ECM, and cellular and mechanical factors [21,26,27,56], and most studies are based solely on 2D induction culture missing the biophysical microenvironments of the ECM. In contrast, 3D system using scaffolds (with interconnected pores) which mimic the structure and function of ECM proteins not only promotes cell adhesion, cell-biomaterial interactions, and cell proliferation [10,38,39], but also facilitates differentiation in skin regeneration [10,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, human ASCs (hASCs) have the advantages of wide sources, convenient access strategies, less damage to patients, rich stem cells in adipose tissue, and low immunogenicity [1,25], indicating that hASCs transdifferentiated into keratinocytes can be a promising strategy to promote wound healing. The differentiation of stem cells depends on the microenvironment of cell growth, named "niche" [21,26,27]. Currently, the main strategy for the differentiation of ASCs into keratinocytes is to add relevant inducing factors to the culture medium [22,23,28] or co-culture with target cells [29].…”
Section: Introductionmentioning
confidence: 99%
“…As previous research efforts highlighted a possible role for EVs in the delivery of certain proteins/growth factor/cytokines, researchers led by Zoltán Wiener (Semmelweis University, Budapest, Hungary) explored the role of EVs in shaping the ISC niche under homeostatic conditions in three‐dimensional human intestinal organoids. In their recent STEM CELLS article, Oszvald et al discovered that the loss of Lgr5‐expressing ISCs due to the absence of EGF, a vital niche signal, could be prevented by the addition of fibroblast‐derived EVs . Further analyses established that both colonic and small intestinal fibroblast‐derived EVs carried the EGF family member amphiregulin on their surface and that blocking EV‐bound amphiregulin inhibited the EV‐induced survival of organoids.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Intestinal organoids provide a faithful in vitro model of the intestinal crypt for research purposes; however, despite a wide range of multilevel analyses, much remains to be understood regarding the niche‐derived signaling programs that control ISCs under homeostatic conditions and in specific disease states. In our first Featured Article published in STEM CELLS this month, Oszvald et al describe the transportation of niche cell‐derived EGF activity by extracellular vesicles (EVs) as a novel intercellular signal transmission mechanism that supports ISC homeostasis . In a Related Article published in STEM CELLS Translational Medicine , Duhachek‐Muggy et al reported on how a piperazine compound protects against the intestinal symptoms of acute radiation syndrome (ARS) by activating Hedgehog signaling and expanding the ISC pool to increase the number of regenerating intestinal crypts …”
mentioning
confidence: 99%